Relations and connections of teacher training in times of complexity: A way for the resignification of the interdisciplinary pedagogical practice - Saker García, Janeth; Barrera Saker, Luz Adriana (IE Revista de Investigación Educativa de la REDIECH, 2021)
The purpose of this essay is to present the relationships that exist around the triad made up of the categories of teacher training, interdisciplinary pedagogical practice and complex world, to respond to the challenges demanded by the planetary society in the emerging context of the education of the XXI century. In this way, this essay addresses teacher training as a structural reference for the development and positioning of education. Likewise, it considers that an interdisciplinary and binding practice requires a teaching paradigmatic rupture, with the capacity to unlearn and undertake transformative actions, through multi-, inter- and transdisciplinary dialogues. The document is made up of four sections: in the first one, relationships and connections are analyzed from uncertainty as a way of rethinking teacher training; in the second part, we move between certainty and uncertainty in a review of thinkers on a path between paradigms; thirdly, we work on the dialogical, epistemological and gnoseological relationship of teacher training; finally, we advance in the understanding of emerging knowledge in the context of a new teacher training. It concludes on the need to learn new relationships in the reconceptualization of teacher-practice training.